Understanding significance and p-values - Bangdiwala, Shrikant I (Nepal Journal of Epidemiology, 2016)
Correction 7th May 2016: p.523, Column 1, second paragraph, line 10 - 'the quantiles at the extremes - say 5%, 1%, which were useful' was changed TO 'the quantiles at the extremes - say 10%, 5%, 2%, and 1%, which were useful'. p.523, Column 2, second paragraph, line 3 - 'this is misconstrued with 'statistical significance' changed TO 'mistaken with 'statistical significance'. Since the p-value is a single index, following the ASA’s statement, we strongly support that it cannot and should not be considered as the sole basis for scientific reasoning. Given the misuses and misconceptions concerning p-values, the recommendation is to present the estimate of the effect, provide a measure of uncertainty of the estimation (e.g. confidence interval), and interpret the results in terms of scientific importance.